Characterization and evaluation of indigenous Saccharomyces cerevisiae strains isolated from South African vineyards - Van der Westhuizen, Theunes Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.) -- University of Stellenbosch, 1999.